2012
DOI: 10.1002/acr.21785
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid‐related changes in body mass index among children and adolescents with rheumatic diseases

Abstract: Objective. To examine the temporal and dose-related effects of glucocorticoids (GCs) on body mass index (BMI) in children with rheumatic diseases.Methods. Children initiating GCs for a rheumatic disease (n ‫؍‬ 130) were assessed every 3 months for 18 months. BMI, weight, and height Z score trajectories were described according to GC starting dosage in prednisone equivalents: high (>1.0 mg/kg/day), low (<0.2 mg/kg/day to a maximum of 7.5 mg/day), and moderate (between high and low) dosage. The impact of GC dosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…The debate about the use of GCs and short stature (short stature leading to a higher BMI compared to normal stature) is ongoing (32), as GCs affect growth in many ways, as summarized by Umławska et al (34). Many studies have shown a significant relationship between short-term and long-term use of GCs and retarded growth (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 96%
“…The debate about the use of GCs and short stature (short stature leading to a higher BMI compared to normal stature) is ongoing (32), as GCs affect growth in many ways, as summarized by Umławska et al (34). Many studies have shown a significant relationship between short-term and long-term use of GCs and retarded growth (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 96%
“…However, we performed a manual validation that demonstrated high sensitivity and specificity of our automated health record search. Additionally, patients in the cohort had the expected changes in BMI and height Z-scores characteristic of children receiving glucocorticoid therapy(34). Third, the majority of our cohort received primary care outside our health network and may have had preventive care not captured in our electronic health record.…”
Section: Discussionmentioning
confidence: 99%
“…BMI is not the only available measure for the assessment of weight gain in children, but its use has been widely adopted 16 , and a recent study of children with rheumatic diseases demonstrated significant increases in BMI z-score associated with treatment with systemic GC 24 . Height and weight measurements were obtained by appropriately trained medical staff members as part of routine care, but a strict protocol for obtaining these measurements was not undertaken.…”
Section: Rheumatologymentioning
confidence: 99%